PEMBUATAN KARTU SANTRI DAN PRESENSI PONDOK PESANTREN AL-KAUTSAR MENGGUNAKAN QR CODE TERINTEGRASI GOOGLE SPREADSHEET - Johan Mohammad Palah; Anugrah, Dias Anugrah; Nurhikmayanti, Kartika Nurhikmayanti; Kartika, Dewi; Wibiwo, Muhammad Editia Kharisma Wibiwo (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
Al-Kautsar Islamic Boarding School Mauk is an Islamic boarding school located in Mauk District, Banten. Currently, attendance for students and teachers is still done manually and there are no student ID cards. Therefore, it is necessary to create student ID cards integrated with Google Spreadsheet for attendance recording. This research uses the Software Development Life Cycle (SDLC) waterfall model, which includes Analysis, Design, Implementation, Testing, and Maintenance. The tools used in this development are QR Generator, Canva, Google Forms, and Google Spreadsheet. The research results in student ID cards equipped with QR Codes that can be scanned using a device, and the attendance will be directly recorded in Google Spreadsheet. The data from the Google Spreadsheet will then be used to recap student attendance every semester.